Parámetros hematológicos de la comadreja overa, Didelphis albiventris (Lund, 1841), de poblaciones silvestres del centro de la Argentina - Tarragona, E.L. (2011)
The objective of this study was to assess haematological parameters in free-ranging white-bellied opossums (Didelphis albiventris) in the central region of Argentina. Total and differential blood cell counts were conducted in thirty-nine captured individuals. The mean (± standard deviation) values obtained were: erythrocytes 5.01 (±2.4) x 10 6 ?L-1, leukocytes: 27,097 (±14,313) ?L-1; neutrophils 7,600 (±7,097) ?L-1 (including immature neutrophils: 794 (±2,738) ?L-1); lymphocytes: 13,110 (±7,541)\n?L-1; basophils: 1,218 (±1,441) ?L-1; eosinophils: 1,983 (±2,458) ?L-1; monocytes: 2,321 (±2,818) ?L-1,. Multivariable statistical analysis showed that neutrophils were strongly associated with sex (p = 0.006). The levels of neutrophils in females doubled that of males. Eosinophils were associated with season. In summer there were significantly greater eosinophils levels than in the winter (p = 0.042). Morphological alterations of erythrocytes were observed in approximately 55% of the blood samples, most of which were stomatocytes and rouleau. A cell type not previously described for this species, annular leukocyte, was also found.